Mikro Konseling Berbasis Refleksi Diri Sebagai Upaya Peningkatan Motivasi Belajar Siswa SMP Berbasis Literatur Review - Mutmainah, Siti; Ni’matul Izzati , Arsya Ma’wa; Anekasari, Rahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning motivation is one of the keys to student success in education; however, low learning motivation poses a significant new problem at the junior high school (SMP) level. This study aims to examine the effectiveness of self-reflection-based micro-counseling as a means of enhancing junior high school students’ learning motivation through a literature review approach. The method used was a literature review, analyzing national and international journal articles published between 2016 and 2026, obtained through Google Scholar, Garuda, and DOAJ. The results of the review indicate that counseling techniques such as cognitive-behavioral therapy (CBT), humanistic counseling, self-management, cognitive restructuring, and feeling reflection techniques have been proven effective in increasing students’ learning motivation. Self-reflection plays a crucial role in helping students recognize their strengths and weaknesses, and contributes to the transformation of motivation from extrinsic to intrinsic. In conclusion, the integration of micro-counseling based on self-reflection can serve as an effective strategy for holistically enhancing junior high school students’ learning motivation.